1992
DOI: 10.1128/aem.58.4.1344-1350.1992
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Frequency, and Diversity of Bacillus thuringiensis in an Animal Feed Mill

Abstract: variety produced different &-endotoxins, revealing a diversity in the strains that was not revealed by serotyping alone. Krieg and Langenbruch (23) and Ellar et al. (15) have suggested that the toxicity of B. thuringiensis to different insect orders could be used for grouping strains into pathotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 29 publications
(18 reference statements)
3
64
0
1
Order By: Relevance
“…It has been also reported, however, that noninsecticidal B. thuringiensis is ubiquitous in natural environments (Ohba and Aizawa 1986;Hastowo et al 1992;Meadows et al 1992;Ohba 1996;Mizuki et al 1999b;Ichimatsu et al 2000). The observations suggest that B. thuringiensis as a species is not characterized by insecticidal activity of parasporal inclusions.…”
Section: Introductionmentioning
confidence: 88%
“…It has been also reported, however, that noninsecticidal B. thuringiensis is ubiquitous in natural environments (Ohba and Aizawa 1986;Hastowo et al 1992;Meadows et al 1992;Ohba 1996;Mizuki et al 1999b;Ichimatsu et al 2000). The observations suggest that B. thuringiensis as a species is not characterized by insecticidal activity of parasporal inclusions.…”
Section: Introductionmentioning
confidence: 88%
“…Soil adjacent to an intensive livestock unit in Warwickshire, UK was subjected to the enrichment method of Johnson and Bishop [12]. For comparison strains were also selected after heat shock (60³C for 30 min) on the basis of their ability to produce insecticidal crystal proteins (ICPs) visible under light microscopy, adapted from Meadows et al [13].…”
Section: Isolation Of B Thuringiensismentioning
confidence: 99%
“…For several decades, a number of insecticidal B. thuringiensis isolates have been recovered from various regions of the world. On the other hand, many studies have reported that noninsecticidal B. thuringiensis strains are more widely distributed than insecticidal ones (Hastowo et al 1992;Meadows et al 1992;Ohba 1996;Mizuki et al 1999b). Therefore, a screening method by optical biosensor was attempted to detect insecticidal strains against certain insects and pests (Okumura et al 2001).…”
Section: Introductionmentioning
confidence: 99%